Cardiac Enzymes (Creatinine Kinase, Troponin I) and Their Gender Relationship - Salwa Muftah Eljamay; Mstafa Suliman Nuesry (المجلة الأفروآسيوية للبحث العلمي, 2024)
Cardiovascular disease (CVD) events in a sex-dependent manner. in apparently healthy males and females across the age span is largely unknown. Aim to find out if their a Relationship between gender and cardiac enzyme (Creatinine Kinase, Troponin I). Material and Methods: Alrazi medical lab from Benghazi collected 506 Blood serum samples, and analysis them by Creatine Kinase (CK) analysis by Biosystems, and A comparison of the Elecsys Troponin T hs assay (MODULAR ANALYTICS E170 analyzer. Result: the frequency for normal result of CKMp up to 25 U L was 316(61.5%), the Higher than 26 U L 190(37.5%), the frequency for normal result of Up To 0.8 ng‎ L was 475(93.9%), and the High More Than < 0.9 ng‎ L, 31(6.1%), and about mean for CKMm and Troponin I(1.38, 1.06), and St. D (0.485, 0.240).In figure (1) illustrate the frequency and the percent of the cases which have high rates of CKMp and TroponuneI 190(37.5%), 31(6.1%) from 506 cases, there is no correlation between CKMm and Troponin I with gender the p-value > 0.05, R(0.076, - 0.031) and there is strong correlation between cardiac enzymes (CKMm and Troponin I), R( 0.244**), p-value < 0.05, the strong **. Correlation is significant at the 0.01 level (P-Value), and there is a relationship between CK - MB and Troponin I because of the correlation (0.244**), X2(30.217a), p-value 0.00 > 0.05. Conclusion: there are no correlations between CKMm and Troponin I with gender and there is a strong correlation between cardiac enzymes CKMm with Troponin I.